DETERMINANT FACTORS OF PURCHASE INTENTION ON GREEN PRODUCT - Diyah, Ida Aryati; Wijaya, Tony (Universitas Brawijaya, Indonesia, 2017)
This research aimed to examine a model which presents effects of man-nature orientation, of healthy consumption lifestyle, of attitude toward a green product, of subjective norm and of purchase behavioural control toward purchase intention of green product. Data collection method of this research used questionnaire, which was arranged through an exploration study based on planned behaviour theory. The sample of this research was housewives as last consumers. In addition, this research was conducted in Yogyakarta, Indonesia. The result showed that man-nature orientation and healthy consumption lifestyle are a predictor for the purchase intention of green product. Man-nature orientation, healthy consumption lifestyle, subjective norm, attitude toward green product and purchase behavioural control give positive contribution for purchase intention of green product. All of the hypothesis in this research were fully supported.